Analysis of the Effect of Infill Density on the Hard Strength of 3D Printing - Azam Muhamad; Muhammad Farhan; Muslimin; Aini Zuhra Abdul Kadir (MBI, 2024)
3D printing technology is becoming one of the most convenient fabrication methods and is bringing about major changes in the manufacturing industry. 3D printing with Fused Deposition Modeling technology makes it possible to produce prototypes and components in a shorter time. It is known that different materials, printing techniques, and printing parameters affect the mechanical properties of printed objects. However, studies on the mechanical properties of 3D printed structures are still limited. This research focuses on the use of thermoplastic materials such as Polypropylene, Acrylonitrile Butadiene Stryrene and plastic composites with glass fiber reinforcement and maleic anhydride, in producing filaments for printing lighter vehicle components. This research conducted a further study of the relationship between two molding parameters, namely infill pattern and infill density, conducted on filament materials that have been determined for their composition. This research uses experimental method by varying five types of infill pattern selected grid, gyroid, hexagon, concentric, cubic with two infill density denisty 50% and 75%. The results were obtained through Brinell hardness testing with ASTM-D785 reference standard. The test results showed that the concentric pattern with sample code B2 got the highest hardness value of 37.7023 Kgf/mm², while the lowest hardness value was obtained by the grid pattern with sample A1 at 16.5912 kgf/mm².